La reanudación y la institucionalización de las relaciones diplomáticas entre México y Bélgica, 1879-1895 - Toledo García, Itzel; Villegas Revueltas, Silvestre (El Colegio de México, A.C., 2017)
Through an analysis of diplomatic correspondence, this article analyzes the reestablishment of diplomatic relations between Mexico and Belgium in 1879 and the various efforts towards rapprochement between the two countries, which had the goal of establishing a legal framework for political, commercial and maritime ties, leading to the signing of the Friendship, Trade and Navigation Treaty in 1895. Examining the resumption and institutionalization of diplomatic ties between these two countries allows us to see how nations adopted standardized international practices as the Americas joined the system of foreign relations ruled by the Western powers. This had a different meaning for each nation. For Mexico, it was important to defend the Juárez doctrine, as well as to institute Díaz’s commercial policies, which had the goal of balancing the economic influence of foreign powers. For Belgium, it was necessary to strengthen its overseas markets in order to be seen as a power on the same level as the empires of the day.